Hidden truth of circulating neutrophils (polymorphonuclear neutrophil) function in periodontally healthy smoker subjects - Chitra Agarwal; Tarun Kumar Baron; Dhoom Singh Mehta (Wolters Kluwer Medknow Publications, 2016)
Context: Tobacco smoking is considered to be a major risk factor associated with periodontal disease. Smoking exerts a major effect on the protective elements of the immune response, resulting in an increase in the extent and severity of periodontal destruction. Aims: The aim of the present study was to assess viability and phagocytic function of neutrophils in circulating blood of the smokers and nonsmokers who are periodontally healthy. Settings and Design: Two hundred subjects in the mean range of 20-30 years of age were included in the study population. It was a retrospective study carried out for 6 months. Materials and Methods: Two hundred subjects were divided into four groups: 50 nonsmokers, 50 light smokers (<5 cigarettes/day), 50 moderate smokers (5-15 cigarettes/day), and 50 heavy smokers (>15 cigarettes/day). Full mouth plaque index, sulcus bleeding index, and probing depths were measured. Percentage viability of circulating neutrophils and average number of phagocytosed Candida albicans were recorded. Statistical Analysis Used: Means and standard deviations were calculated from data obtained within the groups. Comparison between the smokers and nonsmokers was performed by Kruskal-Wallis ANOVA analysis. Comparison between smoker groups was performed using Mann-Whitney-Wilcoxon test. Results: Percentage viability of neutrophils was significantly less in heavy smokers (66.9 ± 4.0), moderate (76.6 ± 4.2), light smokers (83.1 ± 2.5) as compared to nonsmokers (92.3 ± 2.6) (P < 0.01). The ability of neutrophils to phagocytose, i.e., mean particle number was significantly less in light smokers (3.5 ± 0.5), moderate smokers (2.3 ± 0.5), and heavy smokers (1.4 ± 0.5) compared to nonsmokers (4.9 ± 0.7) (P < 0.01) with evidence of dose-response effect. Conclusions: Smoking significantly affects neutrophils viability and phagocytic function in periodontally healthy population.